Цивілістичний аспект правосуддя перехідного періоду в Україні - Мінченко, Раїса Миколаївна; Мінченко, Р. М.; Minchenko, Raisa M. (My University, 2022)
Дана наукова стаття присвячена окресленню загальних напрямків вирішення проблеми відновлення майнових та особистих немайнових прав приватних осіб, порушених внаслідок збройної агресії, як складової правосуддя перехідного періоду в Україні, зокрема, дослідженню можливих юридичних механізмів відшкодування шкоди, заподіяної приватним особам внаслідок збройної агресії у контексті цивілістичного аспекту перехідного правосуддя. Стверджується, що правосуддя перехідного періоду є комплексним поняттям, яке за своїм змістом виходить за межі окремої судової справи або навіть цілої сфери судової практики, адже охоплює цілий комплекс заходів, у який залучені усі гілки влади. Запропоновано виділяти два механізми відшкодування шкоди приватних осіб, заподіяної внаслідок збройної агресії російської федерації: централізований, за якого державними органами створюється спеціальний фонд, який наповнюється грошовими коштами, отриманими від розшуку та реалізації майна країни-агресора та інших джерел, зокрема, за допомоги інших країн-партнерів, а громадяни отримують в адміністративному порядку компенсацію з коштів цього фонду відповідно до встановленого порядку, та децентралізований, який передбачає, що кожна особа, постраждала внаслідок збройної агресії, самостійно здійснює своє право на відшкодування шкоди шляхом звернення до суду. У зв’язку з пріоритетністю централізованого механізму захисту майнових та особистих немайнових прав постраждалих осіб пропонується у справах за позовами про відшкодування шкоди, заподіяної внаслідок збройної агресії російської федерації, встановити обов’язковий досудовий порядок врегулювання ‒ звернення у встановленому адміністративному порядку за отриманням компенсації з коштів державного фонду. І лише у випадках отримання відмови особа вправі звернутися з позовом до суду. Сформульовано пропозиції щодо прийняття Верховною Радою України спеціального закону, який врегулював би всі аспекти процедури відшкодування шкоди, заподіяної внаслідок збройної агресії російської федерації проти України та окреслено основні питання, які мають бути врегульовані цим законом. This scientific article is devoted to outlining the general directions of solving the problem of restoring the property and personal non-property rights of private individuals violated as a result of armed aggression, as a component of transitional justice in Ukraine, in particular, to the study of possible legal mechanisms for compensation for damage caused to private individuals as a result of armed aggression in the context of the civil aspect transitional justice. It is argued that transitional justice is a complex concept, which in its content goes beyond the limits of a separate court case or even a whole field of judicial practice, because it covers a whole complex of measures in which all branches of government are involved. However, domestic scientists do not pay enough attention in their scientific works to the problems of restoring the civil rights of victims, in particular, to the issue of compensation for property, but also moral damage caused to private individuals as a result of armed aggression. Transitional justice encompasses a whole complex of measures, in which all branches of government are involved: legislative, which forms the legislative basis of the mentioned processes, executive, which is entrusted with the duty of investigating war crimes, collecting evidence and recording violations of the rights and freedoms of individuals, and, of course, the judicial branch of government, which, by passing the necessary court decision, tries to restore justice. In the context of the civil aspect of transitional justice, the legal mechanism for compensation for damage caused to private individuals as a result of armed aggression deserves special attention. It is proposed to distinguish two mechanisms for compensation of damage to private individuals caused as a result of armed aggression of the Russian Federation: centralized, under which state bodies create a special fund, which is filled with funds obtained from the search and sale of property of the aggressor country and other sources, in particular, with the help of other countries-partners, and citizens receive administrative compensation from the funds of this fund in accordance with the established procedure, and decentralized, which provides that each person injured as a result of armed aggression independently exercises his right to compensation for damage by applying to court. In connection with the priority of the centralized mechanism for the protection of property and personal nonproperty rights of victims, it is proposed to establish a mandatory pre-trial settlement procedure in cases of claims for compensation for damage caused as a result of the armed aggression of the Russian Federation ‒ an application in the established administrative procedure for receiving compensation from funds state fund. And only in cases of refusal, a person would have the right to file a lawsuit in court. Proposals for the adoption by the Verkhovna Rada of Ukraine of a special law that would regulate all aspects of the procedure for compensation for damage caused as a result of the armed aggression of the Russian Federation against Ukraine were formulated and the main issues that should be regulated by this law were outlined. The author also justifies the necessity to cancel the judicial immunity of the Russian Federation for cases when Ukrainian courts decide on compensation for damage caused as a result of Russian armed aggression. For this purpose, it is proposed to make relevant amendments to the Law of Ukraine “On International Private Law”.
Мінченко Р. М. Цивілістичний аспект правосуддя перехідного періоду в Україні / Р. М. Мінченко // Приватне та публічне право. - 2022. - №3. - С. 27-32. Режим доступу: DOI 10.32845/2663-5666.2022.3.5 ; https://hdl.handle.net/11300/29378
Keywords: цивілістика; цивільний процес; судовий захист; перехідне правосуддя; відшкодування шкоди; збройна агресія; потерпілі особи; civilistic science; civil process; judicial protection; transitional justice; compensation for damage; armed aggression; victims